Oud neg.nr. 279a-f. 'Schwämmerfischer'. Notitie van de beschrijving van de afzonderlijke negatieven' - Haas, Joh. de (1939)
Oud neg.nr. 279a-f. 'Schwämmerfischer'. Notitie van de beschrijving van de afzonderlijke negatieven'.